2005
DOI: 10.1086/444549
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the MECP2 Region Is a Frequent Cause of Severe Mental Retardation and Progressive Neurological Symptoms in Males

Abstract: Loss-of-function mutations of the MECP2 gene at Xq28 are associated with Rett syndrome in females and with syndromic and nonsyndromic forms of mental retardation (MR) in males. By array comparative genomic hybridization (array-CGH), we identified a small duplication at Xq28 in a large family with a severe form of MR associated with progressive spasticity. Screening by real-time quantitation of 17 additional patients with MR who have similar phenotypes revealed three more duplications. The duplications in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
521
3
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(567 citation statements)
references
References 36 publications
26
521
3
9
Order By: Relevance
“…The patients manifested several common phenotypes such as severe MR, muscular hypotonia, absence of speech and recurrent respiratory infections as reported. [15][16][17][18][19] Mapping at dup(X)(q28) of our three families indicated that the smallest region of overlap contained thirteen genes including L1CAM and MECP2 (Supplementary Figure S4a), suggesting that these genes contribute to their …”
Section: Detection Of Nine Benign Cnvsmentioning
confidence: 95%
“…The patients manifested several common phenotypes such as severe MR, muscular hypotonia, absence of speech and recurrent respiratory infections as reported. [15][16][17][18][19] Mapping at dup(X)(q28) of our three families indicated that the smallest region of overlap contained thirteen genes including L1CAM and MECP2 (Supplementary Figure S4a), suggesting that these genes contribute to their …”
Section: Detection Of Nine Benign Cnvsmentioning
confidence: 95%
“…MECP2, X-linked methyl-CpG-binding protein 2 gene at Xq28 is also found to be associated with the developmental delay, MR and fatal infantile encephalopathy in males, and recently it has been reported that low copy number of MECP2 gene confers a clinical phenotype, resulting in MR or developmental delay and altered neurological symptoms (particularly seizures) phenotypes in males. [21][22][23][24] Needless to say, this is perhaps one of the most complex phenotype and the clear picture will emerge when all possible loci and their interactions are well defined.…”
Section: Cnv and Neurological Disordersmentioning
confidence: 99%
“…In contrast to phenotypically well-defined genomic duplications of MECP2 in males (OMIM 300260) and of FOXG1, [25][26][27][28][29][30] the clinical consequences of increased dosage of CDKL5 are poorly understood. Thus far, only larger-sized (8-21 Mb) Xp22 duplications involving CDKL5 have been described, [31][32][33][34] making phenotypic contribution of CDKL5 duplication challenging to dissect.…”
Section: Introductionmentioning
confidence: 98%